Effects of mindfulness-based stress reduction training on rumination in patients with breast cancer - Razieh Bagherzadeh; Rezvan Sohrabineghad; Taiebeh Gharibi; Farkhondeh Mehboodi; Hakimeh Vahedparast (BMC, 2022)
Abstract Background Breast cancer has been a serious public health dilemma for women worldwide, with not only physical and social impairments but also psychological stress responses such as rumination. Rumination is a constant preoccupation with thoughts. The present study aimed to investigate the effectiveness of mindfulness-based stress reduction training in lowering rumination among women diagnosed with breast cancer. Method This randomized controlled trial with a pretest, posttest, control group, and one-month follow-up design included 46 female breast cancer survivors, recruited from the clinics and hematology wards of Bushehr, Iran. The inclusion criterion was that at least three months should have passed since the last chemotherapy/radiotherapy. The participants were randomly assigned to two experimental and control groups. The experimental group received eight sessions of mindfulness-based stress reduction training. A demographic information form and a rumination questionnaire were used for data collection, and the participants completed the questionnaire in the pretest, posttest, and follow-up stages. Chi-square, Mann-Whitney U, and repeated-measures ANOVA were used to analyze the data. P < 0.05 was considered statistically significant. Results There was no significant difference in the rumination scores of the experimental group at three measurement stages. For the control group, the mean rumination scores on the posttest and follow-up were both significantly higher than on the pre-test (P < 0.001). The control group's mean follow-up rumination score was significantly higher than that of the post-test (P = 0.02). A comparison of the two groups adjusted for the baseline showed a significant difference between them in terms of the mean rumination score on the post-test (P = 0.01) and follow-up (P < 0.001). Conclusion The experimental group was more successful in avoiding increased rumination than the control group, an ability that can be attributed to the effect of mindfulness training. The use of this method is recommended because it is non-invasive, non-pharmacological, free from complications, and can be easily performed by women. However, future studies should consider larger samples and long-term follow-ups.